PASTRY: A nursing-developed quality improvement initiative to combat moral distress. (June 2022) - Sarro, Emily Long; Haviland, Kelly; Chow, Kimberly; Sequeira, Sonia; McEachen, Mary Eliza; King, Kerry; Aho, Lauren; Coyle, Nessa; Zhang, Hao; Lynch, Kathleen A.; Voigt, Louis; McCabe, Mary S.
Background: High levels of moral distress in nursing professionals, of which oncology nurses are particularly prone, can negatively impact patient care, job satisfaction, and retention. Aim: "Positive Attitudes Striving to Rejuvenate You: PASTRY" was developed at a tertiary cancer center to reduce the burden of moral distress among oncology nurses. Research Design: A Quality Improvement (QI) initiative was conducted using a pre- and post-intervention design, to launch PASTRY and measure its impact on moral distress of the nursing unit, using Hamric's Moral Distress Scale–Revised (MDS-R.) This program consisted of monthly 60-minute sessions allowing nurses to address morally distressing events and themes, such as clinicians giving "false hope" to patients or families. The PASTRY program sessions were led by certified clinicians utilizing strategies of discussion and mind-body practices. Participants: Clinical nurses working on an adult leukemia/lymphoma unit. Ethical considerations: This was a QI initiative, participation was voluntary, MDS-R responses were collected anonymously, and the institution's Ethics Committee oversaw PASTRY's implementation. Findings: While improvement in moral distress findings were not statistically significant, the qualitative and quantitative findings demonstrated consistent themes. The PASTRY program received strong support from nurses and institutional leaders, lowered the nursing unit's moral distress, led to enhanced camaraderie, and improved nurses' coping skills. Discussion: Measurement of moral distress is innately challenging due to its complexity. This study reinforces oncology nurses have measurable moral distress. Interventions should be implemented for a safe and healing environment to explore morally distressing clinical experiences. Poor communication among multidisciplinary team members is associated with moral distress among nurses. Programs like PASTRY may empower nurses to build support networks for change within themselves and institutions. Conclusion: This QI initiative shows further research on moral distress reduction should be conducted to verify findings for statistical significance and so that institutional programs, like PASTRY, can be created.